2010
DOI: 10.19030/jabr.v26i1.271
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Slack And Performance: The Impact Of Outliers

Abstract: Extending initial theory development and empirical studies conducted in the early

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 0 publications
1
35
0
2
Order By: Relevance
“…Slack resources were historically viewed from the perspective of the organization, and operationalized by investigating factors such as: general and administrative expenses, debt to equity ratios, credit ratings, working capital, R&D expenditures, and the number of employees in a firm (Bourgeois, 1981; Daniel et al, 2004; Mishina et al, 2004; Voss et al, 2008). Several studies have found that slack resources, at least to some extent, enhance firm performance (Daniel et al, 2004; George, 2005; Tseng et al, 2007; Wefald et al, 2010; Goldstein and Iossifova, 2012).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Slack resources were historically viewed from the perspective of the organization, and operationalized by investigating factors such as: general and administrative expenses, debt to equity ratios, credit ratings, working capital, R&D expenditures, and the number of employees in a firm (Bourgeois, 1981; Daniel et al, 2004; Mishina et al, 2004; Voss et al, 2008). Several studies have found that slack resources, at least to some extent, enhance firm performance (Daniel et al, 2004; George, 2005; Tseng et al, 2007; Wefald et al, 2010; Goldstein and Iossifova, 2012).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Although this study investigated slack resources as they relate to performance, it did not consider the influence of a firm's environment. Wefald et al (2010) recognized that the performance‐enhancing benefits of slack resources are dependent on the specific industry for which a firm operates. A meta‐analysis by Daniel et al (2004) documents a positive relationship between slack resources and firm performance, and the results are more significant if the analysis includes industry‐relative performance.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…A company is an organizational entity that processes and accumulates resources [Penrose (1959) in (Zhong, 2011)]. Companies with limited resources find it difficult to gain competitive advantage (Wefald, Katz, Downey, & Rust, 2010). If the company has limited resources, the company that has allocated its resources on social responsibility cannot use its resources to make investments as per its growing opportunity.…”
Section: Slack Resources Theorymentioning
confidence: 99%
“…Further, when considering these relationships, questions arise as to whether -and to what extent -slack resources vary across industries. To date, there is little research specifically focusing on differences in various types of slack across industries (see Wefald et al, 2010 for an exception).…”
Section: Introductionmentioning
confidence: 99%